Pengaruh Kepemimpinan Dan Komunikasi Terhadap Tenaga Kesehatan UPTD Puskesmas Sipayung - Resfita, Desy; Hartono, Budi (Komunika : Jurnal Ilmiah Komunikasi, 2024)
Good leadership and communication are very necessary to achieve organizational goals (puskesmas).Suboptimal implementation of community health center policies can be characterized by a lack ofcommunication, lack of socialization of the community health center program and weak humanresources (HR) in providing services. This can happen because health workers do not fulfill theirduties and responsibilities, so evaluation is needed to produce good performance. The aim of thisresearch is to determine the relationship between leadership and communication and the performanceof health workers at the Uptd Public Health Center in Sipayung. The research method used is aliterature review through analysis of relevant literature. This research aims to obtain leadership andcommunication between health workers who have an impact on patient conditions and provideexplanations related to a deeper understanding of the challenges and solutions in the implementationprocess. The results of the research show that there needs to be improvements in terms of leadershipand communication aspects for health workers so that they influence patients in providing excellentservice so that there is a significant relationship between leadership and communication andperformance. The aim of this research is to provide an overview of effective leadership styles toimprove the quality and quality of health workers. The design of this research is a literature study oneffective leadership and communication styles to improve patient safety. The research results show that an effective leadership style and good communication to improve patient safety is atransformational leadership style. Conclusions in the influence of transformational leadership andcommunication contribute positively to safety climate.